Biological functions of selenium and its potential influence on Parkinson's disease - ELLWANGER,JOEL H. (2016)
ABSTRACT Parkinson's disease is characterized by the death of dopaminergic neurons, mainly in the substantia nigra, and causes serious locomotor dysfunctions. It is likely that the oxidative damage to cellular biomolecules is among the leading causes of neurodegeneration that occurs in the disease. Selenium is an essential mineral for proper functioning of the brain, and mainly due to its antioxidant activity, it is possible to exert a special role in the prevention and in the nutritional management of Parkinson's disease. Currently, few researchers have investigated the effects of selenium on Parkinson´s disease. However, it is known that very high or very low body levels of selenium can (possibly) contribute to the pathogenesis of Parkinson's disease, because this imbalance results in increased levels of oxidative stress. Therefore, the aim of this work is to review and discuss studies that have addressed these topics and to finally associate the information obtained from them so that these data and associations serve as input to new research.